Rekinning Our Kinscapes: Renegade Indigenous Stewarding against Gender Genocide. Issue 3 (1st December 2019) - de Finney, Sandrina; Sam, Shezell-Rae; Adams, Chantal; Andrew, Keenan; McLeod, Kathryn; Lewis, Amber; Lewis, Gabby; Louis, Michaela; Haiyupis, Pawa
Abstract : "Sisters Rising" is an Indigenous-led research project that centers the gender knowledge of Indigenous youth and communities. In this article, members of "Sisters Rising" build on the notion of kinscapes to propose renegade stewardship as a generative concept through which to consider what kinds of responses are required at the community-scholarly-activist level to disrupt conditions of gender-based and sexual violence and racialized poverty that strip Indigenous bodies of sovereignty, land, and cultural connections while targeting us for genocide. Operating from a multimethod research standpoint that is land- and arts-based, community-rooted, and action-oriented, that engages youth of all genders, and that links body sovereignty to decolonization, this work seeks to build political, theoretical, ceremonial, and interpersonal channels that are crucial to restoring dignity with advocacy for and by Indigenous communities.